A Systematic Review on the Value of Infrared Thermography in the Early Detection of Periprosthetic Joint Infections - Scheidt, Sebastian; Rüwald, Julian; Schildberg, Frank Alexander; Mahlein, Anne Katrin; Seuser, Axel; Wirtz, Dieter Christian; Jacobs, Cornelius (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Variations in the temperature of body and skin are symptoms of many pathological changes. Although joint replacement surgery of hip and knee has been very successful in recent decades, periprosthetic infection is a growing problem and the number one reason for revision. While many studies have investigated changes in blood levels, investigation of temperature has not been performed on a regular basis. The objective of this work is to determine whether reference literature exists for the infrared thermographic examination in knee and hip arthroplasty and if reference values can be derived for the methodology or if there is a peri- and postoperative benefit.Material und Methods By means of a systematic online database search and based on the Cochrane, PICOT and PRISMA guidelines, this systematic review retrieved 254 studies. All publications with thermographic examination in arthroplasty of the hip and knee were imbedded. 249 studies were excluded due to the defined inclusion and exclusion criteria and five studies with 251 patients have finally been included in the evaluation process. This was followed by an analysis and discussion of the methodology.Results and Conclusion Infrared thermography is a useful tool in the perioperative care of patients after arthroplasty of the knee and hip joint. The technology is portable, easy to use and non-invasive. Based only on these few publications, values can be derived, which provide a guidance for the thermographic aftercare in arthroplasty surgery.
Keywords: infrared thermography; periprosthetic joint infection; arthroplasty; systematic review